Epicardial fat thickness as a component of early vascular aging in patients with coronary artery disease with borderline coronary stenosis - D. A. Yakhontov; Ju. O. Ostanina; V. L. Lukinov (Российский кардиологический журнал)
Aim. To evaluate the incidence of early vascular aging (EVA) and epicardial fat thickness (EFT) in patients with stable coronary artery disease (CAD) with borderline stenosis.Material and methods. The study involved 201 patients with class 1-3 stable CAD with borderline (50-70%) stenosis. The first group consisted of 57 (28,4%) patients with increased EFT, the second (n=144 (71,6%)) — without increased EFT. EFT was determined by cardiac ultrasound. Vascular wall stiffness was assessed using a VaSera VS-1500N sphygmomanometer manufactured by FUKUDA DENSHI (Japan). Relative telomere length was determined by real-time PCR. All patients underwent coronary angiography.Results. The mean EFT in group 1 was 6,00 [5,00; 6,50] mm, in group 2 — 3,00 [2,30; 4,00] mm (p<0,001). In patients of group 1, hypertension (p<0,001), CAD (p<0,001) in general and myocardial infarction (p=0,003) in particular debuted at a younger age. In both groups, the incidence of obesity, type 2 diabetes, angina, and the intake rate of all four main groups of antianginal drugs did not differ significantly. Early vascular aging was significantly more often detected in the group of patients with stable CAD with borderline coronary artery stenosis and visceral obesity (p<0,001). Relative telomere length was shorter and pulse wave velocity was higher in this group (p<0,001).Conclusion. Patients with stable CAD with borderline stenosis and increased EFT have a higher incidence of EVA, despite the same incidence of obesity, diabetes, and functional class of angina as the group of patients without increased EFT.